Three unusual species of Erythroneurini (Hemiptera: Cicadellidae) with description of new genera - Dmitriev, Dmitry A. (Zootaxa, 2016)
Two new genera of the leafhopper tribe Erythroneurini, Nedotepa gen. n. and Alerrawia gen. n., and three new species, Nedotepa curta sp. n. from Ghana, Alerrawia meliae sp. n. from Kenya, and Musbrnoia linnavuorii sp. n. from Indonesia, are described and illustrated. Nedotepa curta sp. n. has an unusually reduced ovipositor, a feature not previously recorded in Typhlocybinae. Musbrnoia linnavuorii sp. n. has extremely elongated parts of the male terminalia, which remarkably resemble parts of the female ovipositor.